NOTES ON CHIMONOBAMBUSA QUADRANGULARIS (FRANCESCHI) MAKINO (POACEAE: BAMBUSOIDEAE) AS AN INVASIVE ALIEN PLANT SPECIES IN INDONESIA - I Putu Gede Parlida Damayanto; Muhamad Muhaimin (Floribunda, 2017)
Chimonobambusa quadrangularis (Franceschi) Makino is one of the invasive alien plant species in Indonesia. This species originated from South China that was introduced from Japan in the Cibodas Botanical Garden, West Java. This bamboo then escaped the garden and invades Mt. Gede-Pangrango National Park area as recorded in several report. This paper attempt to report the extension of the species distribution in invading with similar modus which also extend alien plant invasion record in Indonesia.